1997
DOI: 10.1074/jbc.272.20.13432
|View full text |Cite
|
Sign up to set email alerts
|

A Sequential Two-Step Mechanism for the Production of the Mature p17:p12 Form of Caspase-3 in Vitro

Abstract: The apoptotic cysteine protease, caspase-3, is expressed in cells as an inactive 32-kDa precursor from which 17 kDa (p17) and 12 kDa (p12) subunits of the mature caspase-3 are proteolytically generated during apoptosis. Two amino acid sequences, ESMD2S (amino acids 25-29) and IETD2S (amino acids 172-176), in the precursor have been defined as the cleavage sites for the production of the p17 and p12 subunits. Using a cell-free assay system, we demonstrate that the caspase-3 precursor appears to be cleaved first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
170
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(176 citation statements)
references
References 32 publications
(53 reference statements)
4
170
1
Order By: Relevance
“…We next attempted to determine the limiting factors for caspase-3 activation in HL-60 and HCW-2 cells using S-100 cytosolic extracts and an in vitro caspase-3 activation assay (Liu et al, 1996;Han et al, 1997;Li et al, 1997). The addition of cytochrome c to the S-100 cytosolic extract from HL-60 cells induced proteolytic activation of the endogen- Unexpectedly, caspase-3 processing also occurred with HCW-2 extracts (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next attempted to determine the limiting factors for caspase-3 activation in HL-60 and HCW-2 cells using S-100 cytosolic extracts and an in vitro caspase-3 activation assay (Liu et al, 1996;Han et al, 1997;Li et al, 1997). The addition of cytochrome c to the S-100 cytosolic extract from HL-60 cells induced proteolytic activation of the endogen- Unexpectedly, caspase-3 processing also occurred with HCW-2 extracts (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…The mature caspase-3 consists of 17 kDa (p17) and 12 kDa (p12) subunits, which are produced from a 32 kDa (p32) precursor (FernandesAlnemri et al, 1994;Nicholson et al, 1995;Tewari et al, 1995a;Liu et al, 1996;Han et al, 1997). Some aspects of the mechanism by which the caspase-3 precursor is converted into the active enzyme are known and in particular endogenous caspase-3 in membrane-free cytosolic extracts from various cell lines can be activated by the addition of exogenous cytochrome c and dATP (Liu et al, 1996;Li et al, 1997) or exogenous cytochrome c alone (Han et al, 1997) under appropriate in vitro assay conditions. Since caspase precursors are present in the cytosol of cells whereas active cytochrome c is located in the mitochondria, these observations suggested that the efflux of cytochrome c from mitochondria into the cytosol during the apoptotic induction process was a key regulatory event in the activation of caspase-3.…”
Section: Introductionmentioning
confidence: 99%
“…25 In this study, we have examined the specificity of M-791 to inhibit caspases in cells, as assessed by caspase processing and substrate cleavage (Figure 1). M-791 caused a concentrationdependent inhibition of the autoprocessing of caspase-3 36 and the cleavage of two caspase-3 substrates, XIAP and cleavage of caspase-9 at D330. 18,37 Furthermore, M-791 inhibited neither the processing of caspase-6, -7 and -8 nor the initial processing of caspase-9 and -2.…”
Section: Discussionmentioning
confidence: 99%
“…When U937 cells overexpressing p27 Kip1 were treated in similar conditions, both procaspase-3 and procaspase-2L remained highly expressed in the cells 24 h after the beginning of cell treatment ( Figure 4a). Activation of caspase-3 involves its cleavage in a p20 and a p12 fragments, then the cleavage of the p20 into a p17 fragment that heterodimerizes with the p12 subunit to form the active caspase (Han et al, 1997). Using a polyclonal antibody that identi®es the p20 and the p17 fragments of caspase-3, we observed that these fragments appeared later and with a lower intensity in p27 Kip1 overexpressing cells compared to mock-transfected cells (Figure 4a).…”
Section: P27 Kip1 Overexpression In U937 Human Leukemic Cells Delays mentioning
confidence: 92%